НАУКОВО-ТЕХНІЧНЕ ЗАБЕЗПЕЧЕННЯ ОРГАНІЗАЦІЇ РОБОТИ ОЕС УКРАЇНИ В СИНХРОННОМУ РЕЖИМІ З ЄВРОПЕЙСЬКОЮ КОНТИНЕНТАЛЬНОЮ ЕНЕРГЕТИЧНОЮ СИСТЕМОЮ ENTSO-E - Кириленко, О.В.; Павловський, В.В.; Блінов, І.В. (Інститут електродинаміки НАН України, Київ, 2022)
Scientific developments, which have been implemented as mandatory to provide a synchronous operation of IPS of Ukraine with the Continental European Power System ENTSO-E are presented. Firstly, it concerns a new level of information maintenance that has been realized by the creation and implementation of a wide range of specialized devices. The features of the construction of information-diagnostic devices are determined. The systems focused on the use of active elements, such as devices and technologies to provide flexible changes in network characteristics, as well as the implementation of electricity conversion to optimize their operation regimes are considered. A special attention was paid to providing a stable operation of the Ukrainian power system, including voltage stability. It covers tools and technologies used to create flexible AC transmission lines. The scenarios for eliminating a major system breakdown with an active power deficit of 1000 MW and other scenarios have been studied. The ways of further research on the development of IPS of Ukraine in the postwar period at the first stages of synchronous operation with ENTSO-E are identified. The paper identifies priority measures and tools aimed to improve the survivability and reliable control of the Ukrainian power system, development of principles and means of adaptation and reconstruction of emergency automatic control of electrical regimes and stability, creating prerequisites for digitalization of the power system. References 35, figures 2.